National and Patriotic Traditions of Upbringing in Russia: History and Modernity; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Erokhin V. K. Vyacheslav Konstantinovich (2016, 2016)
Title screen